Evaluation of seawater salinity effect on proximate composition of the green seaweed Caulerpa cupressoides var. flabellata - Costa, Mariana Santana Santos Pereira; Cordeiro, Sara Lima; Almeida-Lima, Jailma; Costa, Leandro Silva; Rocha, Hugo Alexandre Oliveira (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
Seaweeds as a staple diet has been used in Asian countries for thousands of years. However, in countries like Brazil, consumption of seaweeds as food is still very small due to many reasons. One is the lack of data on Brazilian seaweed’s proximate food composition. This data are very important to any activity related to food science and human nutrition area. The objective of this work was to analyze the chemical composition of the green seaweed Caulerpa cupressoides var. flabellata, collected in two different beaches of the coast of Rio Grande do Norte (Camapum and Búzios). The data showed that the salinity of the water on these two beaches is quite different: The water salinity of Camapum was around 40.5 ppm whereas in Buzios beach was 33.7 ppm. Despite this, the proximate composition of C. cupressoides did not change with increased salinity. Moreover, interestingly, it has low amount of lipids and high amount of proteins, greater even than other edible seaweeds, which indicates that C. cupresoides could be used as protein source for human and animal diet.